Der Stabilitäts- und Wachstumspakt im Zielkonflikt zwischen fiskalischer Flexibilität und Glaubwürdigkeit: Ein Reformansatz unter Berücksichtigung konstitutionen- und institutionenökonomischer Aspekte - Renate Ohr; André Schmidt (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2003)
By applying the concepts of institutional and constitutional economics, this paper addresses the question to what extent a reform of the stability pact will be efficient and appropriate. The starting point of the analysis is the assumption that the stability pact will yield disciplining effects only if it will be credibly applied. Enhancing credibility presupposes that the objectives of the pact are credible themselves and that non-compliance will be contemporarily and strictly sanctioned. The authors conclude that the objectives of the stability pact correspond to the requirements concerning credibility. However, the procedural design of the enforcement mechanism shows substantial deficits. Therefore, an institutional reform of the procedural design following the notion of the separation of powers is proposed, in order to enhance the credibility with respect to the stability pact's enforcement. Suitable institutional mechanisms, which guaranty the compliance with, and the enforcement of, the stability pact, are unalterable prerequisites for transforming the stability pact into an effective disciplining device in the long run.
Keywords: E5; E6; H6; 330; Stabilitätspakt; Europäische Währungsunion; Konstitutionenökonomik